The Use of Padlet through Smart Board in Eighth-Grade Reading Skills at MTs Al Hikam Jombang - Rohmawaty, Evy Nur; Cholilah, Zahirotu; Wicaksono, Meidias Abror (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
The Padlet application is an online platform that can be used as a medium for teaching reading skills to enhance student interaction and facilitate collaboration between students and teachers. This study aims to analyze the use of the Padlet application through Smart Board media in teaching students’ reading skills. The research method used is descriptive qualitative research. The subjects of the study were eighth-grade students at MTs Al-Hikam Jombang. Data and sources were obtained from the Arabic language teacher and the eighth-grade students of MTs Al-Hikam. Data collection techniques included interviews, observations, and documentation. Data analysis was conducted using the theory proposed by Miles, Huberman, and Saldana, employing techniques such as data condensation, data display, and conclusion drawing. The results showed that when viewed from the TPACK framework, the integration of technology (Padlet and Smart Board), pedagogy (collaborative teaching of reading skill), and content (reading skills in Arabic) 1) supports the creation of a holistic learning environment, and 2) the Padlet and Smart Board technologies provide opportunities for teachers to develop more interactive teaching methods tailored to students' needs, allowing students to participate more actively and collaborate in understanding the reading texts. This study recommends the use of similar technologies in teaching other language skills.